2023
DOI: 10.1002/advs.202207650
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of R848 with Sorafenib Enhances Antitumor Effects by Reprogramming the Tumor Immune Microenvironment and Facilitating Vascular Normalization in Hepatocellular Carcinoma

Abstract: Novel promising strategies for combination with sorafenib are urgently needed to enhance its clinical benefit and overcome toxicity in hepatocellular carcinoma (HCC). the molecular and immunomodulatory antitumor effects of sorafenib alone and in combination with the new immunotherapeutic agent R848 are presented. Syngeneic HCC mouse model is presented to explore the antitumor effect and safety of three sorafenib doses alone, R848 alone, or their combination in vivo. R848 significantly enhances the sorafenib an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Remarkably, as key players in the innate immune system, macrophages exhibit elevated expression of major histocompatibility complexes (MHCs) and co-stimulatory molecules upon M1 phenotype activation induced by lipopolysaccharides (LPS) and interferon-γ (IFN-γ). 48–50 Tumor antigens processed by M1 macrophages can subsequently be presented to DCs, 51–54 implying innate interactions between M1 cell membranes and DCs. Furthermore, cell membranes or vesicles derived from M1 macrophages have demonstrated the capacity to repolarize M2 macrophages into the M1 phenotype, 55,56 underscoring the pro-inflammatory attributes of biomembranes originating from M1 macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, as key players in the innate immune system, macrophages exhibit elevated expression of major histocompatibility complexes (MHCs) and co-stimulatory molecules upon M1 phenotype activation induced by lipopolysaccharides (LPS) and interferon-γ (IFN-γ). 48–50 Tumor antigens processed by M1 macrophages can subsequently be presented to DCs, 51–54 implying innate interactions between M1 cell membranes and DCs. Furthermore, cell membranes or vesicles derived from M1 macrophages have demonstrated the capacity to repolarize M2 macrophages into the M1 phenotype, 55,56 underscoring the pro-inflammatory attributes of biomembranes originating from M1 macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Since HCC is diagnosed at advanced stages, it has poor prognosis and a high mortality rate. [1][2][3] HCC is documented for more than 90% of primary liver tumors, mainly due to chronic inflammation. Alcohol abuse, chronic hepatitis viral infections (B and C), and environmental and chemical toxicants are the main leading causes of the national and international spread of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Research targeting the immune system is showing increasing clinical promise in liver cancer treatment (20). One of our recent studies also found that Toll-like receptor agonists can significantly enhance the anti-tumor effect of Sorafenib by reconstructing the tumor immune microenvironment and reshaping the vascular system (21).…”
Section: Introductionmentioning
confidence: 99%